Paris Agreement's Ambiguity About Aerosols Drives Uncertain Health and Climate Outcomes. Issue 5 (17th May 2021) - Polonik, Pascal; Ricke, Katharine; Burney, Jennifer
Abstract: Anthropogenic aerosols are hazardous to human health but have helped offset warming from greenhouse gases (GHGs), creating a potential regulatory tradeoff. As countries implement their GHG reduction targets under the Paris climate agreement, the co‐emissions of aerosols and their precursors will also change. Since these co‐emissions vary by country and by economic sector, each country will face different tradeoffs between aerosol‐driven health or temperature co‐benefits. We combine simple parameterizations of physical processes and health outcomes to examine three idealized climate policy approaches that are consistent with the Paris Agreement targets, which (i) optimize for local air quality, (ii) reduce global temperature change, or (iii) reduce emissions equally from all domestic economic sectors. We evaluate aerosol impacts on premature mortality and global mean temperature change under these three policy approaches and find that by 2030 the three policies yield differences of over 1 million annual premature deaths and global temperature differences of the same magnitude as those from GHG reductions. We also show that implementing equal reductions between all economic sectors can actually result in less beneficial health and temperature outcomes than either of the other options, especially in less industrialized regions. We therefore conclude that aerosol‐related co‐benefits and aerosol accounting guidelines should be explicitly considered in setting international climate policy. Plain Language Summary: We develop a new analytical approach to climate decision‐making that centers the implications of anthropogenic aerosol particulate emissions on climate and human health. Aerosol emissions occur in tandem with greenhouse gases (GHGs) and vary by type of economic activity, so concurrent changes to aerosols from GHG reduction depend on what activities are reduced. We show that, by 2030, the different policy priorities can differ by more than a million premature deaths annually and could cause a similar amount of cooling as from the reduced GHGs, indicating that there are substantial tradeoffs between global climate and local air quality objectives. We conclude that deliberate consideration of particle emissions as part of climate policy could provide additional benefits, especially in less industrialized regions. Key Points: The greenhouse gas emission targets associated with the Paris Agreement carry considerable ambiguity about co‐emitted aerosols By 2030, aerosol ambiguities under Paris Agreement have larger temperature effects than greenhouse gases and change air pollution mortality by 1 million Health and temperature consequences of politically expedient climate policies are worse in less industrialized regions